Nickel-Catalyzed Three-Component 1,2-Carboacylation of Alkenes - Shengzhou Jin; Lanfen Wang; Yinggang Jia; Wenbo Ma; Dingyi Wang (Molecules)
Ketones, prevalent in many biologically significant molecules, require the development of novel methods to synthesize these structures, which is a critical endeavor in organic synthesis. Transition metal catalysis has proven to be an effective method for synthesizing ketones. However, the scope of these substrates remains relatively limited, particularly due to their incompatibility with sensitive functional groups. Herein, we report a Ni-catalyzed three-component 1,2-carboacylation of alkenes, which activates secondary/tertiary alkyl bromides. This method offers significant advantages: simplicity of operation, ready availability of substrates, and broad substrate applicability. A series of experimental studies have helped clarify the key mechanistic pathways involved in this cascade reaction.